Institutional Quality and Sukuk Development: A Study of Five OIC Countries - Nuhbatul Basyariah; Hadri Kusuma; Ibnu Qizam (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The objective of this study is to shed some light on the effect of institutional quality on the development of the global sukuk market. Specifically, this study examines the impacts of the institutional quality that adopts three dimensions of the Worldwide Governance Indicators (WGI), i.e., Rule of Law (RL), Regulatory Quality (RQ), and Government effectiveness (GE) on the global sukuk development of the top-five countries of sukuk issuance, i.e., Malaysia, Kingdom of Saudi Arabia, United Arab Emirates, Indonesia, and Bahrain. Drawing on a quantitative study with the data in the forms of global sukuk issuance from 2002 to 2017, panel-data regression (OLS) and General Method of Moment (GMM) were applied. This study showed that RL and GE have a significantly positive effect on sukuk issuance; however, RQ did not influence the development of the global sukuk market. These results imply that a country that is capable to maintain the institutional quality, especially in terms of rule of law and government effectiveness, will most likely be the country that can successfully develop the sukuk market. These results play a crucial role in filling a research gap among previous studies and provide an empirical evidence of the government’s role and its influence on the sukuk development.